Metabolic Symbiosis Facilitates Species Coexistence and Generates Light-Dependent Priority Effects - Hsu, Veronica; Moeller, Holly V. (Frontiers in Ecology and Evolution, 2021)
Metabolic symbiosis is a form of symbiosis in which organisms exchange metabolites, typically for mutual benefit. For example, acquired phototrophs like Paramecium bursaria obtain photosynthate from endosymbiotic green algae called Chlorella. In addition to facilitating the persistence of P. bursaria by providing a carbon source that supplements P. bursaria’s heterotrophic digestion of bacteria, symbiotic Chlorella may impact competitive interactions between P. bursaria and other bacterivores, with cascading effects on community composition and overall diversity. Here, we tested the effects of metabolic symbiosis on coexistence by assessing the impacts of acquired phototrophy on priority effects, or the effect of species arrival order on species interactions, between P. bursaria and its competitor Colpidium. Our results suggest light-dependent priority effects. The acquired phototroph benefited from metabolic symbiosis during sequential arrival of each organism in competition, and led to increased growth of late-arriving Colpidium. Our findings suggest that understanding the consequences of priority effects for species coexistence requires consideration of metabolic symbiosis.